Implementasi Pelaksanaan UU RI Nomor 2 Tahun 2012 Tentang Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Jamaludin Jamaludin (Jurnal Penelitian Hukum Legalitas, 2015)
The purpose of this study is to investigate the implementation of the implemen- tation of the Land Procurement for Development for Public Interest under Law No. 2 of 2012 on Land Procurement for Development in the Public Interest, which previously only regulated through Presidential Regulation No. 36 Year 2005 on Land Procurement for Development Public Interest as amended by Presidential Decree No. 65 of 2006 and Regulation implementation, the new law is more balance between the interests of government and the interests of society. Methods The approach used in this thesis that the juridical empirical research methods and specifications used in this research is descriptive analy- tic. Data collection research using primary data collection and secondary data. Analysis technique is qualitative descriptive. From the research that has been done shows that the implementation of the Implementation of Land Procure- ment for Development for Public Interest under Law No. 2 of 2012 have not been effectively implemented, due tofrequent change-unlike its implementing regulations stipulated in Presidential Regulation and the Regulation of the Minister of Agrarian and Spatial I Head of the National Land Agency